Smart Technologies for Energy and Environmental Sustainability - Agarwal, Parul; Mittal, Mamta; Ahmed, Jawed; Idrees, Sheikh Mohammad (Green Energy and Technology, 2022)
XII, 273 p. 99 illus., 61 illus. in color.